Preparation method of AlScN piezoelectric film for MEMS sensor

The method optimizes AlScN film preparation for MEMS sensors by using advanced techniques and controlled processes, resulting in high-quality films with enhanced properties for diverse applications.

CN119220928APending Publication Date: 2024-12-31GUOKE HUAXIN (JIANGYIN) SEMICONDUCTOR TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411174775.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Current AlScN film preparation methods for MEMS sensors suffer from low film quality and complex processes, limiting their wide application.

Method used

A method involving substrate preparation, thin film deposition, annealing, patterning, and performance testing is employed, utilizing advanced techniques like molecular beam epitaxy and magnetron sputtering, with optimized parameters and environmental controls to enhance film quality and stability.

Benefits of technology

The method produces high-quality AlScN piezoelectric films with improved piezoelectric properties, thermal stability, and mechanical strength, suitable for MEMS sensors and other applications, offering broad application prospects and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220928A_ABST
    Figure CN119220928A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an Al ScN piezoelectric film for an MEMS (Micro Electro Mechanical System) sensor. The high-quality AlScN piezoelectric thin film is prepared by optimizing thin film deposition, annealing treatment and a patterning process. The method comprises five steps of substrate preparation, thin film deposition, annealing treatment, patterning treatment and performance test and verification. The method has the innovation points that the piezoelectric property, the mechanical strength and the thermal stability of the AlScN thin film are remarkably improved through systematic optimization of process parameters, and powerful technical support is provided for preparation of high-performance MEMS sensors and other piezoelectric devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of AlScN piezoelectric film preparation, and more specifically, to a method for preparing an AlScN piezoelectric film for a MEMS sensor. Background Art

[0002] With the rapid development of micro-electromechanical systems (MEMS) technology, piezoelectric materials are increasingly used in MEMS sensors. Piezoelectric materials are a special type of material that can generate voltage under the action of external force and can also convert voltage into mechanical deformation. This mutual conversion property between mechanical energy and electrical energy makes piezoelectric materials widely used in sensors, actuators, energy harvesters, precision measurement and other fields.

[0003] However, traditional piezoelectric materials such as PZT (lead zirconate titanate) have environmental pollution problems and unstable performance in high-temperature environments.

[0004] As a new type of piezoelectric material, AlScN (aluminum scandium nitride) has excellent piezoelectric properties, thermal stability and environmental protection characteristics, and has gradually become an important material in the field of MEMS sensors. However, the current AlScN film preparation method still has problems such as low film quality and complex process, which restricts its wide application. Summary of the invention

[0005] 1. Technical issues to be solved

[0006] In view of the problems existing in the prior art, the present invention provides a method for preparing an AlScN piezoelectric film for a MEMS sensor, so as to solve the technical problems mentioned in the background technology that the AlScN film preparation method in the prior art still has the problems of low film quality and complex process, which restricts its wide application. Through the method of the present invention, high-quality AlScN piezoelectric film can be successfully grown on a substrate, and its piezoelectric properties, mechanical strength and thermal stability can be optimized.

[0007] (II) Technical solution

[0008] To achieve the above object, the present invention provides the following technical solution: a method for preparing an AlScN piezoelectric film for a MEMS sensor, comprising the following steps in sequence: substrate preparation, film deposition, annealing, patterning, and performance testing and verification;

[0009] The thin film deposition process includes the following steps:

[0010] S1, deposition method: AlScN thin film is deposited using advanced thin film deposition techniques such as molecular beam epitaxy (MBE), magnetron sputtering or chemical vapor deposition (CVD);

[0011] S2, Deposition parameter optimization: Determine the optimal deposition parameters through experimental research, such as sputtering power, nitrogen flow rate, substrate temperature and deposition time. Specific parameters include: sputtering power 100W-200W, nitrogen flow rate 20sccm-40sccm, substrate temperature 200℃-400℃.

[0012] S3, Atomic ratio control of aluminum and scandium: By precisely controlling the evaporation source power of aluminum (Al) and scandium (Sc), the composition ratio and structural uniformity of the AlScN film are ensured to optimize the piezoelectric performance.

[0013] S4, deposition environment control: thin film deposition is performed in a high vacuum environment to avoid impurity contamination and oxidation, and to improve the crystal quality and purity of the thin film.

[0014] The annealing process includes the following steps:

[0015] S1, high temperature annealing: the deposited AlScN film is subjected to high temperature annealing treatment under nitrogen protection, the annealing temperature is 700° C.-900° C., and the annealing time is 0-2 hours.

[0016] S2, heating and cooling control: strictly control the heating and cooling rates to avoid film cracking and substrate deformation, and ensure the structural integrity and stability of the film during annealing.

[0017] S3, Annealing effect: Annealing treatment significantly improves the crystal quality of AlScN film, optimizes its piezoelectric and mechanical properties, and enhances the reliability and service life of the film.

[0018] The present invention is further configured that the substrate preparation comprises the following steps:

[0019] S1, substrate selection: Choose silicon wafer, sapphire wafer or other suitable substrate materials, which have good thermal stability and mechanical strength.

[0020] S2, surface cleaning: remove organic, inorganic and oxide layers on the substrate surface through chemical cleaning and plasma treatment to ensure surface cleanliness and activity.

[0021] S3, pretreatment: preheat treatment is performed in a high vacuum environment to remove residual moisture and contaminants to ensure the cleanliness and activity of the substrate surface.

[0022] The present invention is further configured that the graphical processing includes the following processes:

[0023] S1, photolithography process: photoresist is coated on the surface of the film, and exposure and development are performed through a mask to accurately define the structural pattern and electrode pattern of the sensor.

[0024] S2, etching process: plasma etching or wet etching process is used to remove the area not protected by photoresist to form the required thin film pattern. The etching rate and depth are strictly controlled during the etching process to ensure the accuracy and consistency of the pattern.

[0025] S3, post-processing: removing the photoresist and performing surface cleaning to obtain a high-precision and high-reliability AlScN piezoelectric film structure.

[0026] The present invention is further configured that the performance test and verification comprises the following steps:

[0027] S1, Piezoelectric performance test: The prepared AlScN piezoelectric film is subjected to multiple performance tests, including piezoelectric coefficient, thermal stability and mechanical strength. Through the test, the piezoelectric performance stability and reliability of the film under different stress and temperature conditions are evaluated.

[0028] S2, MEMS sensor application test: The prepared AlScN film is applied to MEMS sensors to conduct performance tests under actual working conditions, including indicators such as sensitivity, response speed, and signal-to-noise ratio. Through the test, the feasibility of the application of AlScN film in high-sensitivity and high-reliability sensors is verified.

[0029] S3, long-term stability test: conduct long-term stability test to evaluate the performance changes of AlScN film in harsh environments such as high temperature, high humidity, vibration, etc., to ensure its long-term stability and reliability in various application scenarios.

[0030] The present invention is further configured that the deposition parameters are set as follows:

[0031] a1, Magnetron sputtering process:

[0032] Sputtering source: Aluminum (Al) and Scandium (Sc) targets.

[0033] Sputtering power: aluminum target 150W, scandium target 50W.

[0034] Nitrogen flow rate: 30sccm.

[0035] Substrate temperature: 300°C.

[0036] a2, deposition time: 2 hours, ensuring the film thickness is between 500nm and 1μm.

[0037] The present invention is further configured such that the annealing temperature is 800°C.

[0038] The present invention is further configured such that the annealing time is 1 hour.

[0039] The present invention is further configured to select silicon wafer (Si), sapphire wafer (Sapphire) or other substrate materials with high thermal stability and mechanical strength. The thickness of the substrate is generally between 500 μm and 1 mm.

[0040] (III) Beneficial effects

[0041] Compared with the prior art, the present invention provides a method for preparing an AlScN piezoelectric film for a MEMS sensor, which has the following beneficial effects:

[0042] 1. Efficient preparation process: By optimizing the deposition parameters and annealing process, the crystal quality and piezoelectric properties of AlScN films are significantly improved, providing an efficient preparation method suitable for large-scale production.

[0043] 2. Environmentally friendly materials: The use of lead-free and non-toxic AlScN materials meets environmental protection requirements and avoids the environmental pollution problems caused by traditional piezoelectric materials.

[0044] 3. Excellent thermal stability: AlScN film has excellent thermal stability and can maintain good piezoelectric and mechanical properties in high temperature environments, making it suitable for applications in various harsh environments.

[0045] 4. Broad application prospects: The AlScN piezoelectric film prepared by the present invention is not only suitable for MEMS sensors, but also can be applied to piezoelectric transducers, surface acoustic wave devices, high-sensitivity pressure sensors and other fields, and has broad application prospects.

[0046] 5. In summary, the present invention significantly improves the performance and reliability of the AlScN piezoelectric film by systematically optimizing the preparation process of the film, providing strong technical support for the preparation of high-performance MEMS sensors and other piezoelectric devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] Figure 1 It is a schematic diagram of the overall process of a method for preparing an AlScN piezoelectric film for a MEMS sensor in the present invention;

[0048] Figure 2 A schematic diagram of substrate preparation in the present invention;

[0049] Figure 3 It is a schematic diagram of thin film deposition in the present invention;

[0050] Figure 4 It is a schematic diagram of annealing treatment in the present invention;

[0051] Figure 5 It is an epitaxial wafer structure without electrodes in the present invention;

[0052] Figure 6The epitaxial wafer structure with upper and lower electrodes in the present invention;

[0053] Figure 7 It is a schematic diagram of device etching in the present invention;

[0054] Figure 8 It is a schematic diagram of the piezoelectric performance test in the present invention;

[0055] Fig. 9 This is a schematic diagram of the current response test in the present invention.

[0056] In the figure: 1. Petri dish; 2. Sample; 3. Deionized water; 4. Acetone / alcohol; 5. Ultrasonicator; 6. Magnetron; 7. Annealing furnace; 8. Crucible; 9. Oxygen source; 10. Substrate; 11. AlScN thin film layer; 12. Top electrode; 13. Bottom electrode; 14. Photolithography machine; 15. Etching plate; 16. Photoresist; 17. Platform; 18. Display end; 19. Probe station; 20. Probe. DETAILED DESCRIPTION

[0057] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0058] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.

[0059] The specific implementation steps of a method for preparing an AlScN piezoelectric film for a MEMS sensor are described in detail below to facilitate a better understanding and implementation of the present invention.

[0060] The present invention provides a method for preparing an AlScN piezoelectric film for a MEMS sensor, comprising the first step of preparing a substrate:

[0061] Step 1, substrate selection:

[0062] Choose silicon wafer (Si), sapphire wafer (Sapphire) or other substrate materials with high thermal stability and mechanical strength. The substrate thickness is generally between 500μm and 1mm.

[0063] Step 2, surface cleaning:

[0064] a1. Use organic solvents (such as acetone and isopropyl alcohol) for ultrasonic cleaning to remove organic pollutants on the surface, wherein the ultrasonic cleaning is achieved by an ultrasonic instrument.

[0065] a2, soak the substrate in hydrofluoric acid (HF) solution to remove the oxide layer on the surface. The treatment time is generally 30 seconds to 1 minute.

[0066] a3, rinse the substrate with deionized water and dry it in a nitrogen environment.

[0067] Step 3, preprocessing:

[0068] a1. Place the cleaned substrate into a vacuum chamber and perform a preheating treatment in a high vacuum environment at a temperature of 200°C for 30 minutes to remove residual moisture and contaminants.

[0069] Step 2 Thin Film Deposition

[0070] Step 1, deposition method:

[0071] a1, AlScN thin film is deposited by molecular beam epitaxy (MBE), magnetron sputtering or chemical vapor deposition (CVD) technology.

[0072] a2, deposition parameter settings:

[0073] Magnetron sputtering process:

[0074] Sputtering source: Aluminum (Al) and Scandium (Sc) targets.

[0075] Sputtering power: aluminum target 150W, scandium target 50W.

[0076] Nitrogen flow rate: 30sccm.

[0077] Substrate temperature: 300°C.

[0078] Deposition time: 2 hours, ensuring film thickness between 500nm and 1μm.

[0079] Step 2, deposition environment control:

[0080] Maintain a high vacuum level in the vacuum chamber, usually below 10^-6Torr, to prevent impurity contamination and oxidation.

[0081] The third step is annealing

[0082] Step 1, high temperature annealing:

[0083] The deposited AlScN film was annealed under nitrogen protection at a temperature of 800° C. for 1 hour in an annealing furnace.

[0084] Step 2, temperature control:

[0085] The heating rate was controlled at 5 °C / min and the cooling rate was controlled at 2 °C / min to avoid film cracking and substrate deformation.

[0086] Step 3, annealing effect evaluation:

[0087] The crystal structure of the films was analyzed using X-ray diffraction (XRD) technique.

[0088] The surface morphology of the films was observed by scanning electron microscopy (SEM).

[0089] Step 4: Graphical processing

[0090] Step 1, photolithography process:

[0091] a1, evenly coat the surface of the film with photoresist, and expose it to ultraviolet light through a mask for 10 seconds.

[0092] a2, developing with developer for 30 seconds to reveal the desired graphic structure.

[0093] Step 2, etching process:

[0094] a1, use plasma etching or wet etching process to remove the area not protected by photoresist. Plasma etching gas is usually argon (Ar) and nitrogen (N2), and the etching time is 5 minutes.

[0095] a2, rinse with deionized water to remove etching residues and dry in a nitrogen environment.

[0096] Step 3, post-processing:

[0097] a1, remove the photoresist using acetone and isopropyl alcohol, and perform ultrasonic cleaning.

[0098] a2, perform surface cleaning to ensure that the patterned film structure is accurate and pollution-free.

[0099] Step 4: Performance testing and verification

[0100] Step 1, piezoelectric performance test:

[0101] a1, Use a piezoelectric tester to test the piezoelectric coefficient of the film and evaluate its piezoelectric performance.

[0102] a2, the piezoelectric response of the film is tested under different temperature and stress conditions to evaluate its stability and reliability.

[0103] Step 2, MEMS sensor application test:

[0104] a1. Apply the prepared AlScN film to MEMS sensors to test their performance indicators such as sensitivity, response speed and signal-to-noise ratio.

[0105] a2. Conduct performance tests under actual working conditions to verify the feasibility of the film in high-sensitivity and high-reliability sensors.

[0106] Step 3, long-term stability test:

[0107] a1, conduct long-term stability tests in harsh environments such as high temperature, high humidity, and vibration to evaluate the performance changes of the film in different environments.

[0108] a2, record and analyze test data to ensure the long-term stability and reliability of the film in various application scenarios.

[0109] Through the above detailed implementation steps, the present invention provides an efficient and reliable method for preparing AlScN piezoelectric film, which significantly improves the performance and reliability of the film and provides strong technical support for the preparation of high-performance MEMS sensors and other piezoelectric devices.

Claims

1. A method for preparing an AlScN piezoelectric film for a MEMS sensor, comprising the following steps in sequence: Substrate preparation, thin film deposition, annealing, patterning, and performance testing and verification, featuring: The thin film deposition process includes the following steps: S1, deposition method: AlScN thin film is deposited using advanced thin film deposition techniques such as molecular beam epitaxy (MBE), magnetron sputtering or chemical vapor deposition (CVD); S2, Deposition parameter optimization: Determine the optimal deposition parameters through experimental research, such as sputtering power, nitrogen flow rate, substrate temperature and deposition time. Specific parameters include: sputtering power 100W-200W, nitrogen flow rate 20sccm-40sccm, substrate temperature 200℃-400℃. S3, Atomic ratio control of aluminum and scandium: By precisely controlling the evaporation source power of aluminum (Al) and scandium (Sc), the composition ratio and structural uniformity of the AlScN film are ensured to optimize the piezoelectric performance. S4, deposition environment control: thin film deposition is performed in a high vacuum environment to avoid impurity contamination and oxidation, and to improve the crystal quality and purity of the thin film. The annealing process includes the following steps: S1, high temperature annealing: the deposited AlScN film is subjected to high temperature annealing treatment under nitrogen protection, the annealing temperature is 700° C.-900° C., and the annealing time is 0-2 hours. S2, heating and cooling control: strictly control the heating and cooling rates to avoid film cracking and substrate deformation, and ensure the structural integrity and stability of the film during annealing. S3, Annealing effect: Annealing treatment significantly improves the crystal quality of AlScN film, optimizes its piezoelectric and mechanical properties, and enhances the reliability and service life of the film.

2. The method for preparing an AlScN piezoelectric film for a MEMS sensor according to claim 1, wherein: the substrate Preparation includes the following steps: S1, substrate selection: Choose silicon wafer, sapphire wafer or other suitable substrate materials, which have good thermal stability and mechanical strength. S2, surface cleaning: remove organic, inorganic and oxide layers on the substrate surface through chemical cleaning and plasma treatment to ensure surface cleanliness and activity. S3, pretreatment: preheat treatment is performed in a high vacuum environment to remove residual moisture and contaminants to ensure the cleanliness and activity of the substrate surface.

3. The method for preparing an AlScN piezoelectric film for a MEMS sensor according to claim 1, characterized in that: Graphic processing includes the following processes: S1, photolithography process: photoresist is coated on the surface of the film, and exposure and development are performed through a mask to accurately define the structural pattern and electrode pattern of the sensor. S2, etching process: plasma etching or wet etching process is used to remove the area not protected by the photoresist to form the required thin film pattern. The etching rate and depth are strictly controlled during the etching process to ensure the accuracy and consistency of the graphics. S3, post-processing: removing the photoresist and performing surface cleaning to obtain a high-precision and high-reliability AlScN piezoelectric film structure.

4. The method for preparing an AlScN piezoelectric film for a MEMS sensor according to claim 1, characterized in that: Performance testing and verification includes the following steps: S1, Piezoelectric performance test: The prepared AlScN piezoelectric film is subjected to multiple performance tests, including piezoelectric coefficient, thermal stability and mechanical strength. Through the test, the piezoelectric performance stability and reliability of the film under different stress and temperature conditions are evaluated. S2, MEMS sensor application test: The prepared AlScN film is applied to MEMS sensors to conduct performance tests under actual working conditions, including indicators such as sensitivity, response speed, and signal-to-noise ratio. Through the test, the feasibility of the application of AlScN film in high-sensitivity and high-reliability sensors is verified. S3, long-term stability test: conduct long-term stability test to evaluate the performance changes of AlScN film in harsh environments such as high temperature, high humidity, vibration, etc., to ensure its long-term stability and reliability in various application scenarios.

5. The method for preparing an AlScN piezoelectric film for a MEMS sensor according to claim 1, characterized in that: Deposition parameter settings: a1, Magnetron sputtering process: Sputtering source: Aluminum (Al) and Scandium (Sc) targets. Sputtering power: aluminum target 150W, scandium target 50W. Nitrogen flow rate: 30sccm. Substrate temperature: 300°C. a2, deposition time: 2 hours, ensuring the film thickness is between 500nm and 1μm.

6. A method for preparing an AlScN piezoelectric film for a MEMS sensor according to any one of claims 1 to 5, characterized in that: The annealing temperature is 800°C.

7. A method for preparing an AlScN piezoelectric film for a MEMS sensor according to any one of claims 3 or 4, characterized in that: The annealing time was 1 hour.

8. The method for preparing an AlScN piezoelectric film for a MEMS sensor according to claim 1, characterized in that: Select silicon wafer (Si), sapphire wafer (Sapphire) or other substrate materials with high thermal stability and mechanical strength, and the substrate thickness is between 500μm and 1mm.